Dhoop aane do- pages plucked from memories by Gulzar - Gulzar (UP Amaryllis, 2024)
Author, poet, lyricist, screenwriter, film director, family man, and winner of every prestigious national and international award for his vast body of work$1 (Bfrom the Jnanpith to the Oscar, there isn$1 (Bt much territory left uncharted by Gulzar. Dhoop Aane Do, in a way, can be considered his autobiography in that it is replete with anecdotes, travel notes, real-life experiences and events that occurred in and shaped his life. The book contains pages plucked from his memories and will take the reader back in time, to his growing-up years, his personal and professional struggles and successes in Mumbai, the experiences he faced during Partition, the different people he met while making films, how the Covid lockdowns affected him, etc. There is poetry too, which underlines the versatility of the author. A deeply personal account made more interesting because of some rare photographs interspersed with the text, Dhoop Aane Do covers his life and career, traversing several eras, thus promising to bring to the reader several unknown facets of Gulzar. It will be an unmissable addition to the treasure trove of books by this literary and cinema legend.s
Keywords: Memoirs; Jnanpith Awardee- Gulzar (2023)